Only very early oxygen therapy attenuates posthemorrhagic edema formation and blood-brain barrier disruption in murine intracerebral hemorrhage - Zhou, Wei; Marinescu, Marilena; Veltkamp, Roland (Neurocritical care, 2015)
Perihematomal edema exacerbates the mass effect of hematoma and contributes to early neurological deterioration after intracerebral hemorrhage (ICH). Oxygen therapy has protective effects on the blood-brain barrier (BBB). We aimed to examine the effects of oxygen therapy on edema formation and BBB permeability after ICH.